Justifying Extraterritorial Regulations of Home Country on Business And Human Rights - Waagstein, Patricia Rinwigati (Indonesian Journal of International Law, 2019)
The regulation of home country to govern business and human rights has been commonly debated. It is argued that home states regulations have a potential role to play in the regulation of multinationals on business and human rights. It particularly can fill the gap due to the extraterritorial nature of MNC operations which requires an integrated regulatory approach and it can also provide alternative forum for victims to human rights violation by corporation to seek justice. The question is in what sense home states should be responsible for violations of human rights by subsidiaries in host countries. What are the justifications and what are the limitations? This article tries to answer those questions by highlighting the debates over the duty bearer, a right or obligations of home countries to impose extraterritorial regulations to other countries.